FORMULATION AND CHARACTERIZATION OF SUSTAINED RELEASE COATED MATRIX GRANULES OF METFORMIN HYDROCHLORIDE - Earle, Radha Rani; Bandaru, Kiran Kumar; Usha A, Lakshmi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Metformin hydrochloride is a biguanide antihyperglycemic agent which is a generally recommended first-line drug for the treatment of diabetes mellitus (Type II). The purpose of this investigation is to prepare sustained release matrix granules of metformin hydrochloride which are coated to extend the drug release over a longer time period. Methods: Metformin hydrochloride granules were prepared by mixing all the dry powders in a V-cone blender and wetting the powder mix with aqueous solution of hydroxypropyl methyl cellulose K100. The prepared granules (MG1-MG5) were investigated for drug release. The batch of granules which exhibited extended release for up to 4 h was coated in a standard coating pan with blends of Eudragit RS and RL to further enhance release period. These were marked as coated metformin granules (CMG3) and CMG4 which were later filled into empty capsules. The granules were characterized for micromeritic properties, percentage yield, particle size distribution, percentage of drug content, and in vitro release of the drug. Results: All the formulations showed percentage yield in the range of 77.66–82.86% and drug content in the range of 78.23–96.62%. CMG3 showed drug release of 97.02% for 12 h. Fourier-transform infrared spectroscopy and differential scanning calorimetry studies indicated that no possible interaction existed between the drug and the polymers used. Scanning electron microscopy images revealed that the granules were spherical in shape with smooth surface and completely covered with a coating of polymer. Kinetic analysis of drug release confirmed that drug release followed zero-order kinetics where it is independent of the concentration. Conclusion: From the results, it was analyzed that design of coated granules employing the polymers used in the present work can produce a sustained release of the drug over a period of 12 h.